Historia diabła Boruty w zbiorze Kazimierza Władysława Wójcickiego „Klechdy, starożytne podania i powieści ludu polskiego i Rusi” - Filipczak-Białkowska, Anita (Diabeł Boruta w dawnej kulturze polskiej, 2021)
The article is devoted to the creature of Boruta devil, created by Kazimierz Władysław Wójcicki in his tome entitled Folk legends, ancient myths and fairy tales of Polish an Russian people’s folk. The tome was published in the 19th century. That was a time when folk culture was on the top of interest. The author is presumed as the pioneer of folk research, also – the creator of folk legend as the literary genre.The article looks into thesis, that communicative context aspects influence the writer, often involuntarily – although the main aim for nineteenth-century folk researchers was to preserve the original version of folk legends, it has not always the reflection in the final versions. Wójcicki not only described the Boruta devil, but also gave him innovative psychological features. This was new for Boruta’s creature, but very specific for nineteenth-century literature, so it is possible to say, that the change was determined by communicative context.